2015
DOI: 10.1016/j.geomorph.2015.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

New insights into the mechanics of fluvial bedrock erosion through flume experiments and theory

Abstract: Please cite this article as: Lamb, Michael P., Finnegan, Noah J., Scheingross, Joel S., Sklar, Leonard S., New insights into the mechanics of fluvial bedrock erosion through flume experiments and theory, Geomorphology (2015), AbstractRiver incision into bedrock drives the topographic evolution of mountainous terrain and may link climate, tectonics, and topography over geologic time scales. Despite its importance, the mechanics of bedrock erosion are not well understood because channel form, river hydraulics, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 121 publications
(197 citation statements)
references
References 163 publications
(250 reference statements)
8
189
0
Order By: Relevance
“…This latter result strongly argues against the hyperconcentration hypothesis. Consistent with the more reasonable volumetric water‐to‐rock ratios suggested by Craddock and Howard [], a water‐to‐rock ratio of 5 × 10 4 yields total flood duration that is very similar to those we estimate from the maximum‐discharge model and more typical of fluvial bedrock incision on Earth [e.g., Lamb et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This latter result strongly argues against the hyperconcentration hypothesis. Consistent with the more reasonable volumetric water‐to‐rock ratios suggested by Craddock and Howard [], a water‐to‐rock ratio of 5 × 10 4 yields total flood duration that is very similar to those we estimate from the maximum‐discharge model and more typical of fluvial bedrock incision on Earth [e.g., Lamb et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Undercutting occurs as a result of scouring of rocks where the water jet impinges the plunge pool, by the combined mechanical action of water and transported sediments [ Mason and Arumugam , ; Stein et al ., ; Bollaert , ; Flores‐Cervantes et al ., ; Pagliara et al ., ], while plucking and toppling occur through the action of bed shear stress applied by water flow upstream of the waterfall brink [e.g., Coleman et al ., ; Chatanantavet and Parker , ; Lamb and Dietrich , ; Lamb et al ., ]. In the case of vertically fractured lithologies, Lamb and Dietrich [] proposed that toppling of rock columns by overland flow could explain the morphology of amphitheater‐headed canyons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shepard and Emery (1941) noted that the largest submarine canyons offshore California are clustered around three mountainous coastal promontories (cf. The effectiveness of this mechanism is likely strongly modulated by the grain size and supply of clastic detritus in the system Lamb et al, 2015;Sunamura, 2018), which is ultimately related to tectonic uplift and the presence of durable bedrock lithologies (Smith et al, 2017). Several classifications have been proposed for submarine canyon littoral connectivity (Romans et al, 2016;Sweet & Blum, 2016); however, no single mechanism has been identified to explain why a select group have avoided being disconnected during post-LGM sea level rise.…”
Section: Submarine Bedrock Incisionmentioning
confidence: 99%
“…(2) 227 13 where s is sediment density, Ui is particle impact velocity, D is grain diameter, and µ is 228 dynamic fluid viscosity (e.g., Lamb et al, 2015). For saltating grains the particle impact 229 velocity is calculated using the equation proposed by Wiberg and Smith (1985); however, 230 expressions are not available for suspended load particle impact velocity.…”
Section: µM 223mentioning
confidence: 99%